LEMBAR KERJA DIRECTED ACTIVITIES RELATED TO TEXTS (DARTS) BERMUATAN MULTIPEL LEVEL REPRESENTASI UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS CALON GURU KIMIA - Imaduddin, Muhamad; Haryani, Sri (Jurnal Inovasi Pendidikan Kimia, 2019)
Understanding the chemistry concept should be demonstrated by the ability to transfer and connect levels of chemical representation. This study aimed to produce DARTs-worksheets containing multiple levels of representation as learning media to improve critical thinking ability. The research used the R&D procedure including define-design-develop stages. One group pretest-posttest design is applied at the develop stage as a form of guarantee of worksheet quality. Data was collected through test techniques (critical thinking ability) as well as non-tests (assessment of the feasibility by experts, students and educators; activity observations; as well as interviews). The subject involved 49 pre-service chemistry teachers at two universities. The results showed that (1) it was produced four worksheets with characteristics that could be viewed from critical thinking skills, DARTs activities, and multiple levels of representation; (2) the DARTs worksheet got a positive rating, the level of "good and very good" for didactic, construction, and technical requirements, and showed the level of readability at the "high" level; (3) worksheets directed activities that indicate an increase in critical thinking ability. Important implications of this study indicated the need to uncover the symbolic learning patterns of chemistry by chemistry teachers in high school, especially compound nomenclature material, chemical reaction equations, and interpretation of graphs, tables, and curves.